Taylor's power law captures the effects of environmental variability on community structure: An example from fishes in the North Sea. Issue 2 (18th December 2018) - Cobain, Matthew R. D.; Brede, Markus; Trueman, Clive N.
Abstract: Taylor's power law (TPL) describes the relationship between the mean and variance in abundance of populations, with the power law exponent considered a measure of aggregation. However, the usefulness of TPL exponents as an ecological metric has been questioned, largely due to its apparent ubiquity in various complex systems. The aim of this study was to test whether TPL exponents vary systematically with potential drivers of animal aggregation in time and space and therefore capture useful ecological information of the system of interest. We derived community TPL exponents from a long‐term, standardised and spatially dense data series of abundance and body size data for a strongly size‐structured fish community in the North Sea. We then compared TPL exponents between regions of contrasting environmental characteristics. We find that, in general, TPL exponents vary more than expected under random conditions in the North Sea for size‐based populations compared to communities considered by species. Further, size‐based temporal TPL exponents are systematically higher (implying more temporally aggregated distributions) along hydrographic boundaries. Time series of size‐based spatial TPL exponents also differ between hydrographically distinct basins. These findings support the notion that TPL exponents contain ecological information, capturing community spatio‐temporal dynamics as influenced by external drivers. Abstract : This research reveals that aspects of community structure beyond species abundances vary with environment. The authors use Taylor's power law to quantify aggregation behaviour to show how the size‐structured North Sea fish community responds with local hydrography, highlighting its utility as an ecosystem metric.